Patient-reported function and quality of life after revision total knee arthroplasty: an analysis of 10,727 patients from the NHS PROMs program - Sabah, SA; Alvand, A; Knight, R; Beard, DJ; Price, AJ (Elsevier, 2021)
Background: The aim of the study was to investigate changes in patient-reported outcome measures (PROMs) after revision total knee arthroplasty (rTKA).